Decreasing of Magnetic Saturation of Yttrium Doped Cobalt Ferrite Prepared by the Sol-Gel Auto-Combustion - Rahardjo, Dwi Teguh; Budiawanti, Sri; Suharno, Suharno; Suryana, Risa; Supriyanto, Agus; Purnama, Budi (Trends in Sciences, 2024)
In this research, a nano-sized cobalt ferrite material doped with Yttrium has been successfully fabricated using the sol-gel method of automatic combustion with variations in low sintering temperatures of 200, 300 and 400 °C. The results of refinement of XRD data using the Rietveld method show that the Yttrium-doped cobalt ferrite compound with a Yttrium concentration molarity of 0.1 possess a cubic crystal system and Fd-3m space group. The increasing annealing temperatures also increase the crystallite size of Yttrium-doped cobalt ferrite with the highest magnitude of 16.05 nm. The FTIR results of the samples indicated the presence of Co-O bonds around wave number 385 cm−1 and Fe-O bonds around wave number 582 cm−1 which are characteristic of the presence of cobalt ferrite compounds. From the VSM measurement results, it can be seen that there is a decrease in magnetic saturation with an increase in annealing temperature. The presence of Yttrium substitution, which takes the place of Fe3+ in cobalt ferrite material, indicates lower saturation magnetization. Image from SEM results showed samples have nanoparticle crystallite size. Evaluation of potential photocatalyst applications using a UV-Visible Spectrophotometer (UV-Vis). For Yttrium doped cobalt ferrite at 200 °C, the best degradation efficiency of Congo Red findings showed a magnitude of 76.10 %; the results are confirmed by the occurrence of the smallest crystallite size (15.11 nm). HIGHLIGHTS Preparation of yttrium-doped cobalt ferrite by the sol-gel auto-combustion method with various annealing temperatures The presence of Yttrium substitution, which takes the place of Fe3+ in cobalt ferrite material, indicates lower saturation magnetization Yttrium-doped cobalt is applied for photocatalytic Congo Red dye in water with the best performance according to the smallest crystallite size GRAPHICAL ABSTRACT